2017
DOI: 10.3390/nano7090261
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver–Silica Composite: Prolonged Antibacterial Effects and Bacterial Interaction Mechanisms for Wound Dressings

Abstract: Infected superficial wounds were traditionally controlled by topical antibiotics until the emergence of antibiotic-resistant bacteria. Silver (Ag) is a kernel for alternative antibacterial agents to fight this resistance quandary. The present study demonstrates a method for immobilizing small-sized (~5 nm) silver nanoparticles on silica matrix to form a nanosilver–silica (Ag–SiO2) composite and shows the prolonged antibacterial effects of the composite in vitro. The composite exhibited a rapid initial Ag relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…et al and Ur Rehman M.A. et al [16,64] described a similar effect to the one reported in this study, where the antibacterial properties increased with the increase of the silver nanoparticle ratio and the humid environment in which the samples were installed, such studies demonstrated the effectiveness of the AgNPs coatings in solid state as an antibacterial system. For the antimicrobial test, an uncoated PEEK film was used as a control in the six plates, which did not present antimicrobial activity.…”
Section: Antibacterial Testsupporting
confidence: 86%
“…et al and Ur Rehman M.A. et al [16,64] described a similar effect to the one reported in this study, where the antibacterial properties increased with the increase of the silver nanoparticle ratio and the humid environment in which the samples were installed, such studies demonstrated the effectiveness of the AgNPs coatings in solid state as an antibacterial system. For the antimicrobial test, an uncoated PEEK film was used as a control in the six plates, which did not present antimicrobial activity.…”
Section: Antibacterial Testsupporting
confidence: 86%
“…There are many factors affecting the potentially hazardous effects of nanomaterials arising from their size, shape, chemical composition, the tendency to agglomerate, solubility, surface area and charge (Nawrotek and Augustyniak 2015;Miller et al 2017;Augustyniak et al 2019). While the toxicity of nanoparticles has been proven by many studies in laboratory conditions (Aruguete et al 2013;Mosselhy et al 2017;Díez-Pascual 2018), their toxicity under the mass production of cementitious composites may vary due to the fact that most of the nanosized admixtures are not stabilized in a working aqueous suspension. In addition, the full dispersion of nanoparticles in aqueous solution is also hindered due to the limited amount of water that is used for the composite production (Sikora et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the published article “Control of the Size of Silver Nanoparticles and Release of Silver in Heat Treated SiO 2 -Ag Composite Powders” [ 1 ] a reference was omitted in the caption of Figure 4b. A citation to [ 2 ] (Reference [12] in the reference list of [ 1 ]) has been added. This does not change the numbering of the reference list in [ 1 ].…”
mentioning
confidence: 99%